Identification of Traditional Village Aggregation Areas from the Perspective of Historic Layering: Evidence from Hilly Regions in Zhejiang Province, China - Mingyu Zhang; Chenying Shen; Weicheng Gu; Qiuxiao Chen (Land, 2023)
The conservation of traditional village clusters, especially those within traditional village aggregation areas, is an important part of historical cultural landscape preservation. With the hilly regions of Zhejiang province as the study area, this study innovatively proposed a traditional village aggregation area identification method from the perspective of historical layering. Because the influence of social economics on the spatial development of villages would gradually lead to spatially geographical features in the village evolution process, this study evaluated eight spatial characteristic indicators from natural geography, socioeconomics, and historical culture to identify ordinary traditional villages based on the threshold value extracted from protective traditional villages. In order to avoid the spatial identification deviation caused by only taking protective traditional villages as samples, we chose them together with ordinary traditional villages to identify 14 traditional village aggregation areas, which were categorized into four types based on regional protection conditions and development potential. This study expands the perspective for understanding the formation of the traditional villages’ spatial characteristics and provides development guidance for traditional village aggregation areas in hilly regions of Zhejiang province.